Oralidade em cena: resenha crítica de filme em podcast - Tiago Silva Pereira Moreira (2024)
This work is the result of a critical reflection on the teaching of orality in the context of the final years of lower secondary education, recognizing the importance of an approach that values orality by incorporating contemporary technological resources as facilitators for active and engaging learning. Thus, this proposal aims to create a podcast for film critical reviews. The primary objective is to discuss the relevance of teaching orality in the school environment and develop a pedagogical proposal focused primarily on teaching the acoustic aspects of oral communication. One of the main questions guiding this investigation is the possibility of systematizing the teaching of a specific oral genre, the review, establishing clear criteria and objectives. The justification for this research lies in the lack of studies and educational resources directed at oral genres, as well as the need to understand the teachable dimensions of a discursive genre in the oral modality. The methodology employed in this proactive work focuses on the development of a didactic proposal based on the concept of discursive genre involving research, analysis, and written and oral textual production using printed and digital educational resources for the proposed activities. Based on the concept of discursive genre, grounded in socio-interactionism and supported by the studies of Dolz and Schneuwly (2004), Aloisa and Suassuna (2020), as well as the concept of multiliteracies by Brian Street (2014), the teaching proposal considers the importance of integrating oral communication with other skills such as reading, listening, writing, and critical analysis of texts, recognizing the frequent multimodal interaction of students who combine written text and audio in their communicative practices. Thus, through this work, we seek to provide students with the opportunity to develop oral communication and critical analysis skills in an engaging manner while offering teachers a practical approach to integrate orality with other language competencies.